Трансформація фінансового обліку: від традиційних методів до цифровізації - Колісник, Олена Пилипівна; Скляров, Даниїл Геннадійович (ПВНЗ "Міжнародний університет бізнесу і права", 2025)
У статті досліджено вплив цифровізації на фінансовий облік та трансформацію традиційних методів під впливом сучасних технологій. Цифровізація підвищує ефективність, прозорість і швидкість операцій. Фінансовий облік еволюціонував від ручного ведення записів до автоматизованих систем, таких як BAS Бухгалтерія, M.E.Doc, COTA. Традиційні методи були трудомісткими та схильними до помилок, тоді як цифрові системи забезпечують швидкість, доступність і автоматизацію. Однак вони мають недоліки: високу вартість, технічні ризики, потребу в кваліфікованих фахівцях. Виклики цифровізації включають безпеку даних, технічні труднощі впровадження, дотримання норм. Інновації, такі як штучний інтелект і цифрові валюти, змінюють фінансовий облік, покращуючи аналітику та управління даними.

The article examines the impact of digitalization on financial accounting and the transformation of traditional accounting methods under the influence of modern technologies. In an era when innovations are penetrating almost all areas of activity, digitalization is becoming a key factor in increasing the efficiency, transparency and speed of operations. Financial accounting, as a key element of any business, has come a long way from traditional methods based on manual record keeping to modern ones using advanced technologies. Traditional methods were characterized by labor intensity, high risk of errors and limited access to information. Despite its historical importance, manual accounting had a number of disadvantages, such as a rigid document flow, limited automation, and low data processing speed. The emergence of the first computerized accounting systems was a revolutionary step, greatly simplifying and speeding up data processing. With the development of technology, accounting programs appeared that automated most accounting processes. The introduction of systems such as BAS Accounting, M.E.Doc, and COTA allowed the integration of all business processes of the company, providing centralized management of financial information. Digital systems for financial accounting have a number of advantages, such as the speed of information processing, easy access to data, and process automation. However, there are also disadvantages, such as high implementation costs, dependence on technology, and the need for qualified specialists. The digitalization of financial accounting faces data security issues, technical difficulties in implementation, and the need to comply with legal and ethical standards. Trends and innovations, such as artificial intelligence and digital currencies, continue to change the financial accounting industry, increasing efficiency and imposing new cybersecurity requirements. The digitalization of financial accounting offers significant benefits, but requires a balance between technological innovation, data security, and regulatory requirements.
Keywords: фінансовий облік; цифровізація; автоматизація; штучний інтелект; облікові системи; технологічні інновації; цифрові валюти; стандарти обліку; financial accounting; digitalization; automation; artificial intelligence; accounting systems; technological innovations; digital currencies; accounting standards